Analysis of Heavy Metal Pollutant in Wangi River Pasuruan and Its Impact on Gambusia affinis - Mohammad Awaludin Adam; Maftuch Maftuch; Yuni Kilawati; Siti Nur Tahirah; Yenny Risjani (Indonesian Journal of Environment and Sustainable Development, 2018)
Pollution that occurred in Pasuruan area’s watershed Wangi–Beujeng river, District of Beji, Indonesia has been initiated in 2007 and continues to this day. The activity was caused by many factors such as the industrial (I), household wastes (II) and agriculture wastes (III) as well as the erosion process.The aims of this study to analyzed the heavy metal pollution that occurs in the Wangi river flow and the effect of gill histology and antioxidant activity on gambusia fish. The research method of observation at river flow and sampling for laboratory test.Three sites were assigned for chemical sampling and tissue histologycal in this study. Fish (Gambusia affinis, local name: Gatul) and water were used as indikatorfrom each site to determine of cadmium (Cd), lead (Pb) and mercury (Hg) concentration using Atomic Absorption Spectrophotometry (AAS). The study was indicated that the streams previously used by residents for daily activities. Results showed level of cadmium (Cd), lead (Pb) and mercury (Hg) in Gambusia affinis exceeded the permissible standard (0.01 ppm Cd;0.03 ppm Pb;0.001 ppm Hg)respectively. Based on histologycal, the tissue showed of damage ofchloride cell (CC) which was used in ion homeostasis process and heavy metal route in grill fish. While protease activities, CAT, MDA and peroxidasse was increased in each sampling area, with significant different (>0.95) between the three sampling sitesKeywords: Chloride cell, Heavy metal, Toxicity, Wangi river